Maple Syrup Urine Disease Complicated with Kyphoscoliosis and Myelopathy - Jia-Woei Hou (Elsevier, 2016)
Maple syrup urine disease (MSUD) is an autosomal recessive aminoacidopathy secondary to an enzyme defect in the catabolic pathway of the branched-chain amino acids (BCAAs: leucine, isoleucine, and valine). Accumulation of their corresponding keto-acids leads to encephalopathy if not treated in time. A newborn male patient was suspected to have MSUD after tandem mass study when he presented symptoms and signs suggestive neonatal sepsis, anemia, and diarrhea. Food restriction of BCAAs was started; however, acrodermatitis enteropathica-like skin eruptions occurred at age 2 months. The skin rashes resolved after adding BCAAs and adjusting the infant formula. At age 7 months, he suffered from recurrent skin lesions, zinc deficiency, osteoporosis, and kyphosis of the thoracic spine with acute angulation over the T11-T12 level associated with spinal compression and myelopathy. After supplementation of zinc products and pamidronate, skin lesions and osteopenia improved gradually. Direct sequencing of the DBT gene showed a compound heterozygous mutation [4.7 kb deletion and c.650-651insT (L217F or L217fsX223)]. It is unusual that neurodegeneration still developed in this patient despite diet restriction. Additionally, brain and spinal magnetic resonance imaging, bone mineral density study, and monitoring of zinc status are suggested in MSUD patients.